2024
DOI: 10.3390/a17010030
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Inspired Neural Network Model of Optical Illusions

Ivan S. Maksymov

Abstract: Ambiguous optical illusions have been a paradigmatic object of fascination, research and inspiration in arts, psychology and video games. However, accurate computational models of perception of ambiguous figures have been elusive. In this paper, we design and train a deep neural network model to simulate human perception of the Necker cube, an ambiguous drawing with several alternating possible interpretations. Defining the weights of the neural network connection using a quantum generator of truly random numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 122 publications
1
6
0
Order By: Relevance
“…Importantly, as with the model presented in this paper, the quantum oscillator financial model outperforms the classical oscillator financial models due to the quantum effects resulting in the formation of discrete energy levels. The same conclusion has been drawn in relevant quantum mind studies, where quantum oscillator models demonstrated significant advantages over the classical models [36,74].…”
Section: The Origin Of Quantum Advantage In Models Of Social Mediasupporting
confidence: 73%
See 1 more Smart Citation
“…Importantly, as with the model presented in this paper, the quantum oscillator financial model outperforms the classical oscillator financial models due to the quantum effects resulting in the formation of discrete energy levels. The same conclusion has been drawn in relevant quantum mind studies, where quantum oscillator models demonstrated significant advantages over the classical models [36,74].…”
Section: The Origin Of Quantum Advantage In Models Of Social Mediasupporting
confidence: 73%
“…In the model, circumstance is represented by interactions between atoms and its influence results in a change in the energy level structure. Finally, the model relies on a rigorous solution of the fundamental Schrödinger equation [35], whose relevance to the domains of psychology and decision-making has been demonstrated [36,74].…”
Section: Quantised Energy Level Model Of the System Of Human Beliefsmentioning
confidence: 99%
“…Another potential link between the physical model proposed in this paper and gender fluidity can be established based on a recent experiment that demonstrated that a perceptual illusion of having an opposite-sex body can be associated with gender fluidity [14]. Intriguingly, optical illusions have also been associated with quantum-mechanical effects [28,31,36,40,74] and they can be both modelled using the concept of qubit (Fig. 1) and the process of magnetisation reversal introduced above (for details we refer the interested reader to [74] and references therein).…”
Section: Discussionmentioning
confidence: 85%
“…For example, artificial deep neural networks built using some principles of quantum physics have been employed to model the human perception of optical illusions (see Refs. [84][85][86] and references therein). In particular, in Ref.…”
Section: Future Workmentioning
confidence: 99%
“…In particular, in Ref. [86], the deep neural network describes the human perception using a synthetic quasi-random time-dependent signal. Subsequently, since the RC algorithm is especially suitable for forecasting complex time series [20], the quantum reservoir can be used to project the output of the deep neural network into the future instances of time, thus dramatically reducing the computational resources needed to train and exploit the more computationally demanding deep neural network.…”
Section: Future Workmentioning
confidence: 99%